Characterization of Nucleotide Misincorporation Patterns in the Iceman's Mitochondrial DNA - Olivieri, Cristina; Ermini, Luca; Rizzi, Ermanno; Corti, Giorgio; Bonnal, Raoul; Luciani, Stefania; Marota, Isolina; De Bellis, Gianluca; Rollo, Franco (PloS one, 2010)
The degradation of DNA represents one of the main issues in the genetic analysis of archeological specimens. In the recent years, a particular kind of post-mortem DNA modification giving rise to nucleotide misincorporation ("miscoding lesions") has been the object of extensive investigations. To improve our knowledge regarding the nature and incidence of ancient DNA nucleotide misincorporations, we have utilized 6,859 (629,975 bp) mitochondrial (mt) DNA sequences obtained from the 5,350-5,100-years-old, freeze-desiccated human mummy popularly known as the Tyrolean Iceman or Otzi. To generate the sequences, we have applied a mixed PCR/pyrosequencing procedure allowing one to obtain a particularly high sequence coverage. As a control, we have produced further 8,982 (805,155 bp) mtDNA sequences from a contemporary specimen using the same system and starting from the same template copy number of the ancient sample. From the analysis of the nucleotide misincorporation rate in ancient, modern, and putative contaminant sequences, we observed that the rate of misincorporation is significantly lower in modern and putative contaminant sequence datasets than in ancient sequences. In contrast, type 2 transitions represent the vast majority (85%) of the observed nucleotide misincorporations in ancient sequences. This study provides a further contribution to the knowledge of nucleotide misincorporation patterns in DNA sequences obtained from freeze-preserved archeological specimens. In the Iceman system, ancient sequences can be clearly distinguished from contaminants on the basis of nucleotide misincorporation rates. This observation confirms a previous identification of the ancient mummy sequences made on a purely phylogenetical basis. The present investigation provides further indication that the majority of ancient DNA damage is reflected by type 2 (cytosine-->thymine/guanine-->adenine) transitions and that type 1 transitions are essentially PCR artifacts.